Reimagining Mythology Through “Feminist Lenses”: A Critical Analysis of Utkarsh Patel's Narrative Techniques - Kumari, Shail; Ali, Zeeshan (Journal of Posthumanism, 2025)
While mythology is a set of folk tales steeped in man-made perceptions that have always identified it as male-dominated throughout time, ancient mythologies did stand upon patriarchal frameworks and celebrated masculinity by relegating their female leads to passivism, submission, or plain victimhood. The reason is that old stories have constructed the genre as a completely male-occupied world in the realm of mythology; their more modern remakes began upending convention and a story, at long last, going beyond its archetypal vision of men only as perpetrators or saviours. Instead, they represent critical viewpoints that re-evaluate the villainous or peripheral female character. This paper examines how postmodern reinterpretations of mythological texts dismantle the ideological limitations of classic patriarchal narratives by examining the alternative discourses that reclaim and celebrate female agency. Among all such reinterpretations, Utkarsh Patel's works dismantle patriarchal ideologies and focus on the reimagining of female figures relegated to the background of history. A possible example of this is the novels Shakuntala: The Woman Wronged (2015) and Satyavati (2019) by Patel, which may be said to offer a feminist reappraisal of mythological heroines. Patel repositions Shakuntala and Satyavati as subjects with agency and power, thereby critiquing the gender prejudices underpinning such myths and appealing for a more inclusive and balanced narration framework. The paper critically analyses the narrative strategies Patel adopted to understand how his remade stories do not merely resist the restrictive boundaries of patriarchal mythology but create space for feminist discourses that dream of a more equitable and egalitarian society.